Correlation of Structure and EBIC Contrast from Threading Dislocations in AlN/Si Films (Phys. Status Solidi B 11/2019). Issue 11 (8th November 2019) - Vacek, Petr; Kostelník, Petr; Gröger, Roman
Abstract : A combination of several microscopy methods, in this case electron beam induced current (EBIC), transmission electron microscopy (TEM) and atomic force microscopy (AFM), allows to correlate structural and electrical properties of AlN films as shown on the cover. AFM reveals the positions of surface terminations of threading dislocations and V‐defects, and EBIC characterizes electrical activities of individual defects. The latter measurements allow to quantify the properties of AlN films and their changes around extended defects. For more information, see article no. 1900279 by Vacek et al.